Students’ Perceptions of the Use of Machine Translation in Learning English for Non-English Department - Nisrina Amalia Rizqi; Intan Permata Hapsari (Journal of English Language and Education, 2026)
Machine translation (MT) has become an increasingly important technology in English language learning, particularly for students with limited English proficiency. However, previous studies have mainly focused on English department students or the technical performance of MT, while the perceptions of non-English department students who study English as a general course remain underexplored. This study aims to investigate non-English department students’ perceptions of using MT in English language learning. A descriptive qualitative design was employed involving 25 undergraduate students selected through purposive sampling. Data were collected through an open-ended questionnaire distributed via Google Forms and analyzed using thematic analysis following Braun and Clarke’s (2006) six-phase procedure, which includes familiarization with the data, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and producing the report. The findings indicate that students generally perceive MT positively, particularly for facilitating comprehension, improving learning efficiency, supporting academic tasks, and providing accessible language assistance. MT also functions as a learning support tool that enhances students’ confidence and understanding. These findings suggest that MT has considerable potential to support English language learning among non-English department students.